Interaction of droplets and particles in the airflow under various ambient conditions; International Journal of Multiphase Flow; Vol. 197 - Islamova A. G. Anastasiya Gomilievna; Klimenko A. Andrey; Shulyaev S. A. Stanislav Antonovich; Strizhak P. A. Pavel Alexandrovich (2026, 2026)
Title screen